Pengaruh Lokasi dan Kurikulum Terhadap Keputusan Orang Tua dalam Memilih Sekolah dengan Brand Image Sebagai Variabel Intervening pada SD Global Jaya Tangerang Selatan - Indra Widhi Susanti; Mohammad Bukhori; Justita Dura (Publikasi Indonesia, 2024)
In the past few years, there has been a rise in private schools’ numbers. There’s also been a phenomenon where more and more parents seek for private schools, especially those who use international curriculum, for their children. The emerging of new privates schools brings tight competition which compells long-established private schools, such as Global Jaya Primary School, to be more vigilant in analyzing their strengths in order to rise above the competition and secures more students. The purpose of this study is to analyze the effect of location and curriculum towards parents’ decision to enroll their children in Global Jaya Primary School through brand image as the intervening variable. This is a quantitative study which uses the primary data from questionnaire to parents. This study uses total population sampling. The data is processed using SEM-PLS. The result shows that (1) location has positive and significant effect on brand image, (2) curriculum has positive and significant effect on brand image, (3) location has direct positive and significant effect on parents’ decision to choose schools, (4) curriculum has direct positive and significant effect on parents’ decision to choose schools, (5) brand image has positive and significant effect on parents’ decision to choose schools, (6) location has positive and significant effect on parents’ decision to choose schools through brand image, (7) curriculum has positive and significnat effect on parents’ decision to choose schools through brand image.